UPAYA PENGUATAN KEMAMPUAN MENULIS MELALUI KORAN MINI KELAS - Dira Annisa; Syafruddin Muhdar; Nofi Hidayanti; Ratih Meiliani; Hilda Raodatul Jannah; Baiq Anggun Maisarah (STKIP Subang, 2026)
This study aims to determine the effect of the classroom mini newspaper program on improving reading interest and writing skills of fifth-grade elementary school students. The method used was classroom observation during literacy learning activities. The results showed that the classroom mini newspaper program was able to increase students’ enthusiasm, active participation, and motivation in reading and writing activities. Students demonstrated improvement in poetry writing skills through better diction and meaning delivery. The program was also supported by creative learning strategies, such as quizzes, educational games, teacher guidance, and appreciation for students’ work. Although several challenges were found, including differences in literacy abilities, limited learning time, and students’ lack of self-confidence, teachers were able to overcome them through varied and conducive learning approaches. Therefore, the classroom mini newspaper program proved to be an effective learning innovation in building literacy culture and improving students’ reading interest and writing skills in elementary schools.